Medical Physics Practice Guidelines ‐ The AAPM's minimum practice recommendations for medical physicists. (4th November 2013) - Chan, Maria F.; Prisciandaro, Joann I.; Shepard, S. Jeff; Halvorsen, Per H.
Abstract : This issue's editorial is an invited commentary authored by Maria F. Chan, Joann I. Prisciandaro, S. Jeff Shepard, and Per H. Halvorsen. It discusses an essential question for practicing medical physicists: What are minimum practice standards and recommendations for clinically active medical physicists? The topic is both timely and essential, as the AAPM and JACMP are beginning to publish community practice standards. This editorial sets the framework and focus of these important articles. Michael D. Mills PhD Editor‐in‐Chief